CONTEMPORARIES AND HISTORIANS ON MATRIMONY IN THE ITALIAN SOCIETY IN XIV-XV: DISCUSSIONS ON THE FAMILY AND MARRIAGE - Irina Anuprienko (Гуманитарные и юридические исследования)
The article examines the views of contemporaries and historians on the relationship of spouses, family and marriage in the Italian society at the turn of the 14th-15th centuries. The analysis is conducted in the light of humanistic views that played a big role not only in the cultural, but also in the political life of the Italian society of the quattrocento period. The culture of Italian Renaissance favored the dialogue as the most significant sociocultural problems were discussed in the form of debates, and then they were transformed into everyday practice and became the norm. The concepts of humanists convey the need for a family as the main motive. Being the foundation of the secular organization of people, in the hands of theorists the family becomes an instrument for understanding and organizing the world, therefore society and the state paid much attention to this aspect. Historians studying the views of Giovanni Morelli, Leon Batista Alberti, Giovanni Boccaccio, Paolo da Certaldo, Kolyuchcho Salutati, Bernardino of Siena and Giannozzo Manetti concluded that humanistic thought produced a significant change in the mentality of society in the following century. The author suggests that the views on marriage were not exclusively Tuscan or Florentine, but it is quite certain that the new family relations originally appeared in Tuscany and Florence, and later on in other European societies.